2014
DOI: 10.1093/hmg/ddu034
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic benefit of lentiviral-mediated neonatal intracerebral gene therapy in a mouse model of globoid cell leukodystrophy

Abstract: Globoid cell leukodystrophy (GLD) is an inherited lysosomal storage disease caused by β-galactocerebrosidase (GALC) deficiency. Gene therapy (GT) should provide rapid, extensive and lifetime GALC supply in central nervous system (CNS) tissues to prevent or halt irreversible neurologic progression. Here we used a lentiviral vector (LV) to transfer a functional GALC gene in the brain of Twitcher mice, a severe GLD model. A single injection of LV.GALC in the external capsule of Twitcher neonates resulted in robus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
78
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(85 citation statements)
references
References 65 publications
7
78
0
Order By: Relevance
“…This is in keeping with our previous observations following intraneural delivery of the same vector (8) or with preclinical (37,38) and clinical (39) applications of similar lentiviral vectors. Rarely reported inflammatory responses (26) were attributed to the reporter gene and not to the intrathecal method of gene delivery or to the vector type.…”
Section: Discussionsupporting
confidence: 91%
“…This is in keeping with our previous observations following intraneural delivery of the same vector (8) or with preclinical (37,38) and clinical (39) applications of similar lentiviral vectors. Rarely reported inflammatory responses (26) were attributed to the reporter gene and not to the intrathecal method of gene delivery or to the vector type.…”
Section: Discussionsupporting
confidence: 91%
“…While treatment of ADA-SCID by HSCT or HSC-GT provides metabolic detoxification in the brain, it might be insufficient to provide the stabilizing allosteric support of ADA to Adora signaling locally. Direct delivery of ADA to the CNS through in vivo gene therapy might be explored as recently proposed for other metabolic disorders4243.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been shown that molecules regulating protein sorting and degradation within the endocytic and autophagic pathways (fig. 3a) generally cause disorders associated with lysosomal dysfunctions [57,58,59,60,61,62,63,64,65] and are also a hallmark of several neurodegenerative diseases, including ALS, PD and AD (fig. 3b) [66].…”
Section: Correlation Of Als and Neurodegenerative Disease Mimics As Cmentioning
confidence: 99%